2010
DOI: 10.1007/s00134-010-2048-5
|View full text |Cite
|
Sign up to set email alerts
|

Variables affecting leakage past endotracheal tube cuffs: a bench study

Abstract: Cuff leakage varies greatly among ETT types and is affected by cuff pressure, PEEP, PIP, and mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 21 publications
1
48
0
1
Order By: Relevance
“…A trachea model, as described by Pitts et al, 19 consisting of silicon tubing (28-cm length and 2.3-cm internal diameter) was used for this study. The trachea model was lightly clamped in a stationary vertical position, intubated without lubrication, and connected to a test lung.…”
Section: Part 2: 8-h Stationary Trialmentioning
confidence: 99%
“…A trachea model, as described by Pitts et al, 19 consisting of silicon tubing (28-cm length and 2.3-cm internal diameter) was used for this study. The trachea model was lightly clamped in a stationary vertical position, intubated without lubrication, and connected to a test lung.…”
Section: Part 2: 8-h Stationary Trialmentioning
confidence: 99%
“…[8][9][10]13 However, the study's measurement conditions did not include PEEP or mechanical ventilation, so the benefit of the new cuff in the presence of positive-pressure ventilation is unknown, given that PEEP influences the rate of fluid leak. 9,[12][13][14]16 The selection of a round, inflexible acrylic tube for a trachea model, although common in the literature, 3,8,11 may not translate in vivo, because the most common tracheal cross-sectional shape is an ellipse. 6 Young et al reported that, with an acrylic tube as the trachea model, all the endotracheal tube cuffs tested demonstrated leak, but only 45% of the tubes had a leak when examined in a porcine trachea.…”
Section: See the Original Study On Page 1095mentioning
confidence: 99%
“…2,[7][8][9][10][11] The flow of secretions past the cuff is determined by the height of the column above the cuff, the angle of inclination, the cuff inflation pressure, and the tracheal pressure applied by the ventilator. 9,[12][13][14] The addition of PEEP has been shown, both in vivo and in vitro, to counterbalance this hydraulic force and to limit the leakage past the cuff. 9,13,14 The endotracheal tube and cuff were recently examined for their contributions to VAP.…”
mentioning
confidence: 99%
See 2 more Smart Citations